Dysbiotic Biofilms Deregulate the Periodontal Inflammatory Response. (May 2018) - Herrero, E.R.; Fernandes, S.; Verspecht, T.; Ugarte-Berzal, E.; Boon, N.; Proost, P.; Bernaerts, K.; Quirynen, M.; Teughels, W.
Periodontal diseases originate from a dysbiosis within the oral microbiota, which is associated with a deregulation of the host immune response. Although little is known about the initiation of dysbiosis, it has been shown that H2 O2 production is one of the main mechanisms by which some commensal bacteria suppress the outgrowth of pathobionts. Current models emphasize the critical nature of complex microbial biofilms that form unique microbial ecologies and of their change during transition from health (homeostatic) to disease (dysbiotic). However, very little is known on how this alters their virulence and host responses. The objective of this study was to determine differences in virulence gene expression by pathobionts and the inflammatory host response in homeostatic and dysbiotic biofilms originating from the same ecology. Quantitative polymerase chain reaction was performed to quantify the pathobiont outgrowth. Expression analysis of bacterial virulence and cellular inflammatory genes together with cytokine enzyme-linked immunosorbent assays were used to detect differences in bacterial virulence and to analyze potential differences in inflammatory response. An increase in pathobionts in induced dysbiotic biofilms was observed compared to homeostatic biofilms. The main virulence genes of all pathobionts were upregulated in dysbiotic biofilms. Exposure of these dysbiotic biofilms to epithelial and fibroblast cultures increased the expression of interleukin (IL)–6, IL-1β, tumor necrosis factor–α, and matrix metalloprotease 8, but especially the chemokine CXCL8 (IL-8). Conversely, homeostatic and beneficial biofilms had a minor immune response at the messenger RNA and protein level. Overall, induced dysbiotic biofilms enriched in pathobionts and virulence factors significantly increased the inflammatory response compared to homeostatic and commensal biofilms.